Persuasive in preaching discourse of mamah dedeh and aa beraksi on indosiar - Fajar, Fajar Yogaatmaja; Dawud; Martutik (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Language has a highly vital role in life. One of them is the use of persuasion. Persuasion used in preaching must try to coax, influence, and change the mindsets of the preaching participants in the activity of preaching. This present study was categorized as aqualitative research using the theoretical orientation of discourse analysis. The data research were in the forms of words, phrases, clauses, and sentences. It was obtained from the persuasive preaching discourses which were transcribed from the show program of “Mamah Dedeh and AA Beraksi” on Indosiar channel downloaded via Youtube in March, 2019. The results of the discourse analysis of Mamah Dedeh's preaching in Indosiar include, (1) persuasive diction include (a) (a) the choice of words to invite by encouraging and ordering, (b) the choice of words to prohibit by preventing and forbidding, (c) the choice of words to threaten by fear and detrimental; (2) the content of persuasive messages includes (a) the content of the message inviting to take action, recommending, and ordering (b) the content of the prohibition message by commanding and requesting (c) the content of the threat message with self harm and harm to others, and; (3) persuasive message strategies include (a) rational reinforcement strategies with facts and logic, (b) emotional evocation strategies by emphasizing sadness and emphasizing anxiety, and (c) mixed strategies by emphasizing bad and emphasizing good